The Use of Stem and Root Barks Extracts from Synadenium glaucescens (Euphorbiaeceae) as Acid Base Indicators: Experimental Investigation - James G. Mayeka; Faith P. Mabiki (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Presently, the conduct of acid-base chemical interactions necessitates the use of industrially produced indicators, which are linked to contamination of the environment. This circumstance necessitates the exploration of natural sources for further acid-base indicators. The purpose of this research was to investigate at the acid-base indicating capacity of Synadenium glaucescens extracts. To investigate S. glaucescens’ indicating capacity, extracts from the leaves, stems, and root barks were tested for colour change, reversibility, pH range, and effectiveness during titration using strong and weak acids and bases. The findings revealed that only the indicators derived from stem and root bark extracts had indicating capacity, since they were able to change colour due to pH change. The pH range of the two indicators was 2.9 to 12.7, indicating that they were more universal indicators. While in acidity and alkalinity circumstances, both indications could be clearly inverted. At the end points of the titration, the colour changed significantly. The mean titre of the two indicators were ranging from 24.3 ± 0.31 to 25.4 ± 0.75 and 18.9 ± 0.17 to 24.1 ± 0.05, respectively with their colour change from brick red to colourless and orange to colourless, respectively. The end points acquired by stem and root bark indicators correspond to the end points obtained by phenolphthalein and methyl orange, which are standard indicators. As a result, the stem and root bark extracts can be used as an acid-base indicator. More research might be done to make paper indicators and extract the pure compound that is responsible for S. glaucescens’ signalling capacity.